Learn a language for free: Recreational learning among adults. (October 2017) - Chik, Alice; Ho, Jenifer
Abstract: Research increasingly shows that language learning is a complex process that cannot be contained within the four walls of a classroom. However, we do not have enough empirical knowledge of what learners do if they decide to learn a language on their own for free. Learning a language for free is an especially attractive idea in the current context of greater online access to learning resources and communities. This paper reports on two projects conducted in 2010 and 2015 that followed three language learners to explore non-English foreign language learning beyond the classroom. In both projects, participants used only freely available public resources. Our findings showed an increased preference for structured non-formal learning resources, and a decline in do-it-yourself (DIY) learning objects as learners moved from one life stage to another during the five-year period. We argue for further research on language learning which occurs entirely beyond the classroom. We also argue for expanding the research conversation to include life transitions to better understand language learning beyond the classroom.